Studi tentang Kolaborasi antara Perawat dan Tim Kesehatan dalam Meningkatkan Pelayanan Keperawatan - Nurambiya, Nurambiya (Barongko: Jurnal Ilmu Kesehatan, 2025)
Interprofessional collaboration is a key element in improving the quality of health services, particularly in nursing care that emphasizes a holistic approach to patient needs. This study aims to examine the role of collaboration between nurses and healthcare teams in enhancing the quality of nursing services. The research method used was a literature review and qualitative descriptive analysis of previous studies. The results indicate that effective collaboration among nurses, physicians, midwives, pharmacists, and other health professionals can increase patient satisfaction, accelerate recovery, and reduce the risk of medical errors. The discussion highlights the importance of open communication, mutual respect for professional roles, and managerial support in fostering teamwork. The conclusion of this study is that good interprofessional collaboration significantly improves nursing service quality and patient safety.